2016
DOI: 10.1186/s40413-016-0118-z
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to positively- and negatively-charged plasma cluster ions impairs IgE-binding capacity of indoor cat and fungal allergens

Abstract: BackgroundEnvironmental control to reduce the amount of allergens in a living place is thought to be important to avoid sensitization to airborne allergens. However, efficacy of environmental control on inactivation of airborne allergens is not fully investigated. We have previously reported that positively- and negatively-charged plasma cluster ions (PC-ions) reduce the IgE-binding capacity of crude allergens from Japanese cedar pollen as important seasonal airborne allergens. Cat (Felis domesticus) and fungu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…We previously demonstrated that allergens from Japanese cedar pollen and fungus were degraded by PCI treatment in an experimental setting [9,10]. In the present study we confirmed that the PCI treatment also degraded HDM allergens in a manner similar to that reflected by the previous studies' results, by conducting an SDS-PAGE (sodium dodecyl sulfate-polyacrylamide gel electrophoresis) analysis (data not shown).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…We previously demonstrated that allergens from Japanese cedar pollen and fungus were degraded by PCI treatment in an experimental setting [9,10]. In the present study we confirmed that the PCI treatment also degraded HDM allergens in a manner similar to that reflected by the previous studies' results, by conducting an SDS-PAGE (sodium dodecyl sulfate-polyacrylamide gel electrophoresis) analysis (data not shown).…”
Section: Discussionsupporting
confidence: 81%
“…We previously demonstrated that PCI treatment effectively inactivated atomized Japanese cedar pollen and fungal allergens [9,10]. Those results prompted us to examine the effect of PCIs on HDM allergens, one of the most important airborne environmental allergens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations